The Correlation between Physical Activity and the Menstruation Cycle in Adolescents at Warga Senior High School Surakarta - Naibaho, Winny Novietta K; Riyadi, Slamet; Suryawan, Arif (Nexus Kedokteran Komunitas, 2014)
Backgrounds: Recently, many teenagers have an irregular menstruation periods. Physical activity is one of the risk factor that increase the incidence of menstruation periods irregularity. High Schoolâs students had a lot of variation in daily physical activities. This research aimed to determine the correlation between physical activity and the menstrual cycle in adolescents at Warga High School Surakarta. Methods: This research used descriptive analytical study by the cross sectional design. The subject of the research were female students of X and XI grade at Warga High School in Surakarta that taken by purposive random sampling technique. Independent variable of this research was physical activity whichÂ  was measured by International Physical Activity Questionnaire (IPAQ). Dependent variable of this research was menstruation cycle which was measured by menstruation cycle questionnaire. The size of the sample were 90 female students who were divided into 3 group based on their intensity of physical activities. These 3 groups were divided again based on their menstruation cycle. The collected data were analysed with Chi Square formula and Coeffisient Contiquenency (CC). Results: The result of Chi Square analysis was 0,037 as p value and the value of Q was 0.261 . Conclusions: There was correlation between physical activity and menstruation cycle in adolescents at Warga Senior High Schools Surakarta but the correlation between these two variables was less closely related. Keywords: physical activity, menstruation cycle, adolescentsÂ